Peranan Bahan Baku terhadap Optimalisasi Hasil Produksi pada Usaha Mikro di Kabupaten Lebak - Jauhar Latifah; Suheri .; Ratu Neneng Rozbiati; Lita Mulyati (E-Journal Studia Manajemen, 2012)
This study aims to examine and analyze the effect role of raw material on optimization production at micro business in Kampung Desa Cibuluh Mugijaya Cigemblong Lebak. This study uses a combination of research methods (mixed methods) between quantitative and qualitative research methods. Desing study based on reports production of raw materials and optimization of production at micro business. The population used in this study is 25 palm sugar artisans. Purposive sampling method was used conducted research. The results showed that Three is effect of raw material on optimization of production.